Faktor - Faktor Yang Memengaruhi Employee Performance Pada Karyawan PT. XYZ - Rahman, Rifqi (Seminar Nasional Manajemen, 2026)
This study aims to analyze the factors affecting employee performance at PT. XYZ. This study was motivated by the decline in employee performance in 2025 compared to 2024 at PT. XYZ. This study uses a quantitative approach by collecting data through questionnaires, observations over four months (February-May 2025), and interviews with several employees. The sampling technique used saturated sampling with a total of 55 employee respondents. PT. XYZ. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS 4 software. The results of the study show that emotional intelligence has no effect on employee performance. Emotional intelligence has a positive and significant effect on self-efficacy. Emotional intelligence has a positive and significant effect on job satisfaction. Self-efficacy has no effect on job satisfaction. Self-efficacy has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Self-efficacy mediates the effect of emotional intelligence on employee performance. Job satisfaction mediates the effect of emotional intelligence on employee performance. Self-efficacy does not mediate the effect of emotional intelligence on employee performance.